(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents information about folk games on the basis of historical sources, archaeological, ethnographic, pedagogical materials and numerous scientific literature, articles, reports on the background of the general picture of historiography and source study as a periodic-chronological problem.